A new species of Charinus Simon, 1892 (Arachnida: Amblypygi: Charinidae) from Israel and new records of C. ioanniticus (Kritscher, 1959) - Miranda, Gustavo S.; Aharon, Shlomi; Gavish-Regev, Efrat; Giupponi, Alessandro P.L.; Wizen, Gil (European Journal of Taxonomy, 2016)
A new species of Charinus is described from Israel and new localities for C. ioanniticus are reported. Charinus israelensis sp. nov. is a cave dwelling species with extremely small median eyes, no median tubercle and reduced lateral eyes. It is similar to C. ioanniticus, which occurs in nearby areas, but can be differentiated by the shape of the carapace, the number of pedipalp spines and the development of the eyes. A detailed comparison is made between the two species, including pictures, drawings and scanning electron micrographs. Charinus ioanniticus is reported here from several new localities in Israel and Turkey. Identification keys to the Charinus species groups and to the species of the bengalensis group are provided.